2015
DOI: 10.1002/2015ja021819
|View full text |Cite
|
Sign up to set email alerts
|

Severe and localized GNSS scintillation at the poleward edge of the nightside auroral oval during intense substorm aurora

Abstract: In this paper we study how GPS, GLONASS, and Galileo navigation signals are compromised by strong irregularities causing severe phase scintillation (σϕ>1) in the nightside high‐latitude ionosphere during a substorm on 3 November 2013. Substorm onset and a later intensification coincided with polar cap patches entering the auroral oval to become auroral blobs. Using Global Navigation Satellite Systems (GNSS) receivers and optical data, we show severe scintillation driven by intense auroral emissions in the line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 108 publications
4
74
1
Order By: Relevance
“…In a case study of another event by Jin et al (2014), patches that had entered the auroral region (auroral blobs) were directly connected to the strongest scintillations. In the case study by van der Meeren et al (2015), scintillations were not observed for patches outside of the region of auroral emissions/particle precipitation, but strong scintilllation was observed in association with patches co-located with strong auroral emissions/particle precipitation. In-situ observations of patches by Moen et al (2012) indicate that particle precipitation is a driver of plasma instabilities that form structures on scales that cause scintillation in GNSS signals.…”
Section: Auroral Electrojetmentioning
confidence: 99%
See 2 more Smart Citations
“…In a case study of another event by Jin et al (2014), patches that had entered the auroral region (auroral blobs) were directly connected to the strongest scintillations. In the case study by van der Meeren et al (2015), scintillations were not observed for patches outside of the region of auroral emissions/particle precipitation, but strong scintilllation was observed in association with patches co-located with strong auroral emissions/particle precipitation. In-situ observations of patches by Moen et al (2012) indicate that particle precipitation is a driver of plasma instabilities that form structures on scales that cause scintillation in GNSS signals.…”
Section: Auroral Electrojetmentioning
confidence: 99%
“…Patches have also been connected to the occurrence of substorms (Nishimura et al 2013;Zou et al 2014). In a recent multi-instrument case study by van der Meeren et al (2015), the patches were only associated with scintillations when they were located in the region of auroral precipitation. They suggest that a combination of both patches and energetic particle precipitation may be required in order to produce strong scintillations in the auroral region, but that their work alone does not present enough evidence to make a firm conclusion regarding this.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charged particles from the solar wind and magnetosphere, mostly electrons and protons, precipitate in the upper atmosphere and dissipate their energy by generating the auroral emission. The nightside auroral events have been studied by many researchers since the last several decades and it has been found that in the auroral region, strong ionospheric scintillations are observed (Coker et al, 2004;Mitchell et al, 2005;De Franceschi et al, 2008;Hosokawa et al, 2014;Jin et al, 2014;van der Meeren et al, 2014van der Meeren et al, , 2015; and the references therein). Cusp region ionospheric irregularity dynamics which gives rise to pre-noon hour scintillation and cycle slips have been found to be associated with the polar cap patches during the solar minimum (Prikryl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Their brightening and diming is the signature of the open and closed field lines respectively. Many other important recent research investigations (e.g., Liu et al, 2015;Lyons et al, 2015;Prikryl et al, 2015;van der Meeren et al, 2015;Hosokawa et al, 2016;Jin et al, 2017 etc. ) related with the auroral emission have been successfully carried out suing the SuperDARN radar network.…”
Section: Introductionmentioning
confidence: 99%